Copy of treaty no. 6 made 9th September, 1876, between Her Majesty the Queen and the Plain and Wood Cree Indians and other tribes of Indians at Fort Carlton, Fort Pitt and Battle River [electronic resource]. - Canada. Treaties, etc. 1876 Sept. 9. ([S.l. : s.n., 1876)
Cover title. "Copy, Treaty no. 6, Indian Office"--p. [3]. Electronic reproduction. Mode of access: Internet. 44